Ketahanan Mortar Ringan Campuran Gula Aren dan Ragi pada Suhu Tinggi: Narrative Review - Shelly Christina; Daniel Kristanto; Fahri Hafisuddin; Monita Olivia (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
Lightweight mortar is specific type mortar that made with adding up a foaming agent. Lightweight mortar has a lot of pores or cavity that filled by air which causing reduction of the mortar’s weight. With its high porosity, the lightweight mortar has better heat insulation than common mortar. There are many pieces of research and applications of lightweight mortar in the last few years, and this review is focusing on lightweight mortar that made with a natural additive which has good high-temperature resistance. There are many additives can be used such as yeast and palm sugar. Yeast is the microorganism that can be used as a foaming agent because it can produce carbon dioxide (CO2) that create a lot of pores on the mortar through the glycolysis process. Palm sugar is disaccharide groups sugar which is sucrose that consists of glucose and fructose. Glucose can reduce gypsum consumption in mortar and ettringite formation. Besides, sugar contains lignin which can increase the bonding strength of mortar’s components. This study proofs that innovation of lightweight mortar with organic additive has a long-term potency with its durability on high temperature.